EFEKTIVITAS PENGGUNAAN SMARTPHONE DALAM AKTIVITAS BELAJAR MAHASISWA ILMU KOMUNIKASI UNIVERSITAS SLAMET RIYADI SURAKARTA - Nurnawati Hindra H, Egie Apriani Putri, Dian Esti Nurati & (Transformasi, 2016)
New technologies in the form of communication is often known as smartphones. Communicationtechnologies in the form of a smartphone is a phenomenon of the most unique and interesting inits use. Smartphone that is easy to carry anywhere now no longer know the ages and walks oflife, even called now smartphones have become